STRATEGI PENERAPAN CUSTOMER RELATIONSHIP MANAGEMENT STUDI KASUS : BEBILUCK.COM - Titin Fatima; Lusi Fajarita (Bit (Fakultas Teknologi Informasi Universitas Budi Luhur), 2012)
Every businessperson in every line of business wish their product to be the best for consumers. There is no doubt that any business activity is nowadays focusing in achieving satisfaction. To mantain good relationship between the company and consumers, the CRM (Customer Relationship Management) concept emerged. The CRM concept would better be supported by technology, which enables the availability, appropriate, accurate, and fast of integrated information whom consumers need. Technology nowadays, internet technology in particular, giving the CRM concept superiority. From the front to back-office section. The purpose of this writing is an analysis of the system implementation strategies into the e-commerce business. As a case study of the CRM application, a line of business which it's process is using internet technology is chosen. An e-commerce.Keywords: CRM, Internet Technology, E-Commerce